Posicionamentos e conflitos sobre os impactos de empreendimentos imobiliários na orla fluvial de Belém: o caso de Edifício Premium - NEWAR, Cyane Luana Melo (2019)
This work problematizes positions and conflicts regarding the impacts of real estate developments on the Belém do Pará waterfront, through the Premium Building case. It shows that, despite all the current law sandall the proposal back to the river, present in the local urban policies, the Premiun Building of Construtora Quadra wase rected on the banks of Guajará Bay, in spite of the current environmental protection laws. The discussion of the issue demanded the understanding of the agents producing the urban space, the role of real estate capital, the process of verticalization and the production of space on the border of Belém. Discourses and conflicts about the appropriation of the Belém border as a socially produced space presupposed news surveys published in newspapers of local circulation in 2014, the same year in which the Building, the focus of the discussion, attracted the attention of people favorable and contrary to its construction. By means of these positions and the conflicts of which they are carriers, it is sought to problematize the contradictory production of the production of the space in the riverbank of Belém.